SAR Image Object Detection and Information Extraction: Methods and Applications - Zhongzhen Sun; Xiangguang Leng; Mingjin Zhang; Haohao Ren; Kefeng Ji (Remote Sensing)
Synthetic aperture radar (SAR) is now recognized as a critical source of observational data in domains such as military reconnaissance, maritime monitoring, and disaster response, owing to its ability to deliver fine spatial resolution and broad-area imaging irrespective of weather or daylight conditions [...]